Proactive Personality and Entrepreneurial Intentions among Nigerian Students: Moderating Role of Perceived Institutional Support - Ojeleye, Yinka Calvin; Ojeleye, Chioma Ifeoma; Rafiu Falola, Kareem; Abdullahi, Aisha (Oeconomica Jadertina, 2023)
The youth unemployment especially among graduates in Nigeria is at all-time high. The study explored the moderating role of perceived institutional support in the relationship between proactive personality and entrepreneurial intentions among students. The study employed survey and cross-sectional research design. The study employed purposive sampling technique 1000 pieces of questionnaire were administered students four federal universities in Kaduna, Kano, Sokoto and Zamfara states out of which 627 were valid and used for the analyses. The study used statistical package for social sciences (SPSS) to run the preliminary analyses such as detection of missing value, outliers, multicollinearity and test of normality. Structural equation model (SmartPLS) was used to run the measurement and structural models. The findings revealed that proactive personality and institutional support have positive and significant effect entrepreneurial intentions among students in the selected institutions. Furthermore, institutional support significantly moderated the relationship between proactive personality and entrepreneurial intentions The study recommended that institutions should support the students to develop entrepreneurial intentions. One way of achieving this is through the inclusion of entrepreneurial education, entrepreneurial guidance and counselling to boost entrepreneurial intentions. Future studies can also conduct a longitudinal study as against the cross-survey employed by this study to properly ascertain the established relationship or otherwise of the constructs of study.
Keywords: Institutional support; Entrepreneurial intentions; Proactive personality; Theory of Planned Behaviour